Physiological and Biochemical Effects of Echium Amoenum Extract on Mn2+-Imposed Parkinson Like Disorder in Rats - Leila Sadeghi; Farzeen Tanwir; Vahid Yousefi Babadi (Tabriz University of Medical Sciences, 2018)
Purpose: Manganism is a cognitive disorder take places in peoples are exposed to environmental manganese pollution. Overexposure to manganese ion (Mn2+) mainly influences central nervous system and causes symptoms that increase possibility of hippocampal damages. Methods: In this study rats were administrated by two different doses of MnCl2 and behavioral and physiological consequences were evaluated. We also investigated effects of E. Amoenum on Mn2+-imposed toxicity by behavioral, biochemical, immunoblotting and histological studies on hippocampus tissue. Results: Results showed metal overexposure increases oxidative stress mainly by lipid peroxidation and reactive oxygen species overproduction. Histological studies and caspase 3 analyses by immunoblotting revealed Mn2+ induced apoptosis from mitochondrial-dependent pathway in the presence of low metal dose. This study provides evidence that oral administration of E. amoenum extract inhibited manganese neurotoxicity by oxidative stress attenuation and apoptosis reduction that lead to improved depression like behavior. Plant extract also increased catecholamine content in Mn2+ treated hippocampus. Conclusion: As molecular and pathophysiological effects of E. amoenum, it could be considered as a pre-treatment for Parkinson and Parkinson like disorders in high-risk people.